Hubungan Karakteristik Usahatani Terhadap Produksi Kelapa Dalam di Desa Punggur Kapuas Kecamatan Sungai Kakap Kabupaten Kuburaya - Hartanto, Prakas Dwi; Yurisinthae, Erlinda; Suharyani, Anita (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The largest contribution to coconut production came from Sungai Kakap sub-district, amounting to 22,172 per hectare in 2020, however the process of cultivating coconut in Sungai Kakap sub-district only relies on passed down experience and methods of cultivating coconuts according to existing knowledge without any innovation, thus posing a threat that affects production results. and the welfare of farmers so that the coconut farming business they run becomes difficult to develop. The aim of this research is to analyze the characteristics of coconut farming and to analyze the relationship between farming characteristics and coconut production in Punggur Kapuas Village, Sungai Kakap District. The method used in this research uses quantitative descriptive methods. The data sources used in this research are primary data and secondary data. The location of this research was determined purposively, namely based on the consideration that in Punggur Kapuas Village, Sungai Kakap District, there are deep coconut farming businesses, so it helps that the data obtained will provide more representative values. Based on the results of the analysis of coconut farming in Punggur Kapuas village, Sungai Kakap district, it has the potential to be developed intensively and sustainably. Support from the characteristics of farmers who are of productive age and have long farming experience will be able to motivate farmers to improve their farming. The relationship between farming characteristics and coconut production, namely the characteristics of farming experience, has a significant value of 0.005 = 0.05, meaning there is a correlation between the farming experience variable and coconut production. The characteristics of land area have a significance of 0.000 < 0.05, meaning that there is a correlation between the variable land area and coconut production. Meanwhile, the variables age, education and number of dependents have a significant value of > 0.05, meaning there is no correlation with coconut production.